Circuit bodyweight training: does it affect increasing arm muscle endurance and archery accuracy in pandemic conditions? - Betrix Teofa Perkasa Wibafied Billy Yachsie; Suharjana Suharjana; Ridho Gata Wijaya; Ahmad Nasrulloh (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
Restrictions on community activities due to the spread of the Covid-19 virus have changed sports in Indonesia, forcing athletes to practice independently in their respective homes with training programs created by coaches. This study aims to find out the effect of circuit body weight training on arm muscle endurance and archery accuracy of archery athletes. This research is an experimental method of one group pretest-posttest design. This study employed purposive sampling with the criteria of elite archery athletes, still in high school, male, and willing to participate. Total of 12 athletes was given treatment with 8 movements for 16 meetings. The instrument is a holding bow digit test for arm muscle endurance, while archery accuracy uses 50 meters of archery. The collected data were examined for normality and homogeneity, then followed with t-test with the result that t count = 0.00 less than t (0.05). Based on the results, it is concluded that circuit bodyweight training positively improves arm muscle endurance and accuracy of archery athletes. Therefore, giving circuit bodyweight training can be used as a recommendation for physical exercise to increase arm muscle endurance and archery accuracy in archery athletes.